TOWARD TRAFFIC FLOW MODELLING APPROACHES UPDATING (World Science, 2020)
The paper describes an analysis of the traffic flow characteristics and individual vehicle characteristics used for design decisions. Traffic flow statistic obtained with the help of Weigh in Motion System is presented. The brief analysis of the main traffic flow characteristics is performed, the need for traffic flow modelling approaches updating is outlined.